Kinetics studies of uranium sorption by powdered corn cob in batch and fixed bed system - Mohamed A. Mahmoud (Journal of Advanced Research, 2016)
Sorption of uranium (VI) from aqueous solution onto powdered corn cob has been carried out using batch and fixed-bed technique. The experimental results in batch technique were fitted well with pseudo second-order kinetics model. In the fixed bed technique, Thomas and Bohart–Adams models were evaluated by linear regression analysis for U(VI) uptake in different flow rates, bed heights and initial concentrations. The column experimental data were fitted well with Thomas mode (r2 = 0.999), but the Bohart–Adams model (r2 = 0.911), predicted poor performance of fixed-bed column.